2007
DOI: 10.1158/1078-0432.ccr-06-2309
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Bevacizumab and Irinotecan in Recurrent Malignant Glioma

Abstract: Purpose: Recurrent grade III-IV gliomas have a dismal prognosis with minimal improvements in survival seen following currently available salvage therapy. This study was conducted to determine if the combination of a novel antiangiogenic therapy, bevacizumab, and a cytotoxic agent, irinotecan, is safe and effective for patients with recurrent grade III-IV glioma. Experimental Design: We conducted a phase II trial of bevacizumab and irinotecan in adults with recurrent grade III-IV glioma. Patients with evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
686
8
14

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 987 publications
(737 citation statements)
references
References 42 publications
29
686
8
14
Order By: Relevance
“…Thus, the relatively poor results in this study could be due to the fact that the combination partners in the PBV and PCV regimens contribute to this efficacy or that temozolomide pre-treated patients are less likely to respond to nitrosoureas at recurrence. Altogether, treatment results with ACNU are inferior compared with the recent studies with bevacizumab/irinotecan [18,19] or doseintensified temozolomide [17] and also showed considerable hematotoxicity. We do not propose that our data exclude a role of ACNU in certain subgroups of patients or within combined treatments in recurrent glioblastoma.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Thus, the relatively poor results in this study could be due to the fact that the combination partners in the PBV and PCV regimens contribute to this efficacy or that temozolomide pre-treated patients are less likely to respond to nitrosoureas at recurrence. Altogether, treatment results with ACNU are inferior compared with the recent studies with bevacizumab/irinotecan [18,19] or doseintensified temozolomide [17] and also showed considerable hematotoxicity. We do not propose that our data exclude a role of ACNU in certain subgroups of patients or within combined treatments in recurrent glioblastoma.…”
Section: Discussionmentioning
confidence: 74%
“…In the latter study, patients who had received temozolomide as a first-line therapy benefited from a dose-intensified re-exposure, too. Another phase II study evaluated the use of bevacizumab, a monoclonal antibody to vascular endothelial growth factor, in combination with irinotecan, a topoisomerase inhibitor [18,19]. This study reached a PFS-6 of 46% in patients with recurrent glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, no direct comparisons are available and the trials evaluating bevacizumab plus temozolomide were conducted in part in highly pretreated patient populations [72][73][74]. Five phase II trials evaluated the combination of irinotecan with bevacizumab [91][92][93][94][95], two trials added a third combination partner, cetuximab [96] or carboplatin [97]. PFS-6 rates ranged between 28 and 50.3% and median OS between 6.7 and 9.7 months.…”
Section: Bevacizumab Monotherapy and Combination Regimensmentioning
confidence: 99%
“…A prospective phase 2 study using every-3-week dosing of bevacizumab at a dose of 15 mg/kg in 61 patients with World Health Organization grade 3 or grade 4 glioma demonstrated no obvious differences in patient outcomes compared with contemporary studies using every-2-week dosing at 10 mg/kg, 37 thus allowing for flexibility in patient scheduling without clinical detriment. Several phase 2 trials of bevacizumab-based combinations have also been reported for recurrent glioblastoma (Table 1), 27,28,32, including bevacizumab with irinotecan, irinotecan plus cetuximab, irinotecan plus carboplatin, etoposide, fotemustine, sorafenib, temozolomide, erlotinib, and temsirolimus. 27,28,32,[38][39][40][41][42][43][44][45][46][47] In addition, several retrospective studies have also been reported combining bevacizumab and irinotecan; carboplatin; carboplatin and cetuximab; carboplatin, etoposide, and ifosfamide; lomustine; carmustine; etoposide; or temozolomide.…”
Section: Early Study Of Bevacizumab In Patients With Recurrent Glioblmentioning
confidence: 99%
“…Several phase 2 trials of bevacizumab-based combinations have also been reported for recurrent glioblastoma (Table 1), 27,28,32, including bevacizumab with irinotecan, irinotecan plus cetuximab, irinotecan plus carboplatin, etoposide, fotemustine, sorafenib, temozolomide, erlotinib, and temsirolimus. 27,28,32,[38][39][40][41][42][43][44][45][46][47] In addition, several retrospective studies have also been reported combining bevacizumab and irinotecan; carboplatin; carboplatin and cetuximab; carboplatin, etoposide, and ifosfamide; lomustine; carmustine; etoposide; or temozolomide. [48][49][50][51][52][53][54][55][56][57][58] Although these small studies are not easily compared due to their size and various patient populations, the consensus to date has been that no combination significantly surpasses the outcomes of bevacizumab monotherapy for recurrent glioma.…”
Section: Early Study Of Bevacizumab In Patients With Recurrent Glioblmentioning
confidence: 99%